The Relationship among Transformational Leadership, Organizational Learning, and Organizational Innovation: A Case Study in Asian Manufacturing Food Industry - Mohamed RADZI, Che Wan Jasimahbt Wan; HUI, Huang; JENATABADI, Hashem Salarzadeh; KASIM, Farihah Abu; RADU, Son (Asian Journal of Empirical Research, 2013)
The main purpose of this study to find out the relationship among transformational leadership (TL), organizational learning (OL), and organizational innovation (OI) in manufacturing food industry in east of Asia countries include China, Taiwan, and Malaysia. Structural equation modeling (SEM) was used to test the research hypotheses from168 manufacturing food companies. Our research model contains three constructs, and the results showed there is positive impact between constructs. Also, Organizational learning is a mediator in the linkage between transformational leadership and organizational innovation.